Persistent right aortic arch and absent left subclavian artery in a seven‐week‐old English Springer Spaniel. Issue 1 (1st March 2021) - Rowan, Conor; Bilek, Andrea; Böhler, Alexandra
Abstract: A seven‐week‐old English Springer Spaniel presented with recurrent vomiting that began with the introduction of solid food. No musculoskeletal issues such as lameness were identified. On radiography, focal dilation of the oesophagus cranial to the heart base was identified. CT angiography confirmed the suspected persistent right aortic arch. A concurrent absent left subclavian artery was identified that has not been reported in detail previously. In addition, a bicarotid trunk and right subclavian artery branched directly from the aortic arch in lieu of a brachiocephalic trunk. A collateral blood supply via an intercostal and vertebral artery furnished the branches of the absent left subclavian artery. The dog developed aspiration pneumonia, deteriorated and was euthanised.